Development of an Oxygen-Sensitive Hydrogel for Monitoring Oxygen Diffusion in Tissue Engineering (Transactions on Additive Manufacturing Meets Medicine, 2025)
Additive manufacturing has revolutionized the development of biomaterials by enabling precise control over structural properties at the microscale. In tissue engineering, oxygen transport remains a major challenge, particularly in the development of vascularized artificial tissues. To address this, we present an oxygen-sensitive hydrogel fabricated using one-photon polymerization and two-photon polymerization (2PP), designed for real-time observation of oxygen diffusion characteristics. The hydrogel, based on polyethylene glycol diacrylate (PEGDA), incorporates oxygen-sensitive dyes to enable a colorimetric response to varying oxygen concentrations.The hydrogel formulation and fabrication were optimized for biocompatibility, tunable permeability, and stable optical readout. Diffusion experiments were conducted to analyze the oxygen transport behavior under different conditions, including variations in hydrogel thickness and environmental oxygen levels. The results demonstrate that the hydrogel allows for controlled oxygen diffusion, provides a measurable response to oxygen gradients and that the hydrogel’s permeability can be tailored via additive manufacturing. This approach offers a valuable tool for studying oxygen supply in engineered tissues and could enhance the design of microfluidic organ-on-a-chip systems.Our findings indicate that oxygen-sensitive hydrogels hold great potential for improving in vitro tissue models by enabling precise monitoring of oxygen distribution, which is essential for cell viability and function. Future research will focus on integrating these hydrogels into microfluidic systems to simulate vascularized environments more accurately.
Keywords: Additive Manufacturing; Two-Photon Polymerization; Oxygen-Sensitive Hydrogel; Tissue Engineering; Oxygen Diffusion; Microfabrication; Biomaterials; Organ-on-a-Chip; Polyethylene Glycol Diacrylate (PEGDA); Regenerative Medicine